2017
DOI: 10.1002/2017ef000609
|View full text |Cite
|
Sign up to set email alerts
|

Statistical wave climate projections for coastal impact assessments

Abstract: Global multimodel wave climate projections are obtained at 1.0° × 1.0° scale from 30 Coupled Model Intercomparison Project Phase 5 (CMIP5) global circulation model (GCM) realizations. A semi‐supervised weather‐typing approach based on a characterization of the ocean wave generation areas and the historical wave information from the recent GOW2 database are used to train the statistical model. This framework is also applied to obtain high resolution projections of coastal wave climate and coastal impacts as por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 45 publications
3
82
0
1
Order By: Relevance
“…Even though storm surge projections studies are limited, the same dipole between islands was found in previous analysis on wave global projections (Hemer et al ., ; Semedo et al ., ; Camus et al ., ), leading to a storm surge decrease in the north island while an increase in storm surge is predicted in the south island. In the analysis developed at the Port of Tauranga, Bell et al .…”
Section: Discussionmentioning
confidence: 97%
“…Even though storm surge projections studies are limited, the same dipole between islands was found in previous analysis on wave global projections (Hemer et al ., ; Semedo et al ., ; Camus et al ., ), leading to a storm surge decrease in the north island while an increase in storm surge is predicted in the south island. In the analysis developed at the Port of Tauranga, Bell et al .…”
Section: Discussionmentioning
confidence: 97%
“…In this study we used dynamical models to study the behavior of waves around NW European coasts, which requires a large amount of computational effort, compared to studies done by statistical downscaling methods (e.g., Camus et al, 2017). Therefore, we decided to choose one well-tested GCM with good performance over NW Europe rather than using several models in an ensemble.…”
Section: Selection Of a Climate Model For Wave Model Forcingmentioning
confidence: 99%
“…Hemer and Trenham () show that high performance of GCMs for standard climate variables does not imply high performance for GCM‐forced wave simulations. Camus et al (), using weather typing and statistical downscaling, informed by a historical data set of wave data, showed how this method could be used to provide high‐resolution coastal impact assessment, including additional variables such as wave period and direction as well as SWH. Their results show that the global multimodel projections of the SWH and peak period are consistent with changes obtained in previous studies, that is, a decrease in mean wave height and peak period for the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…The 2, 4, and 8 year recurrence interval water levels were estimated for respective sea level rise RCP scenarios. Current research suggests that coastal water levels during extreme events are rising with an increase in wave height and sea level (e.g., Hemer et al 2013;Camus et al 2017;Mentaschi et al 2017;Vousdoukas et al 2018). Statistical tests of the tidal gauge data indicated no significant change in extreme sea levels over the period of record.…”
Section: Model Data Inputsmentioning
confidence: 94%